2005
DOI: 10.1158/0008-5472.can-05-2620
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Coexistent Mutations of PIK3CA and PTEN Genes in Endometrial Carcinoma

Abstract: The phosphatidylinositol 3V-kinase (PI3K) pathway is activated in many human cancers. In addition to inactivation of the PTEN tumor suppressor gene, mutations or amplifications of the catalytic subunit A of PI3K (PIK3CA) have been reported. However, the coexistence of mutations in these two genes seems exceedingly rare. As PTEN mutations occur at high frequency in endometrial carcinoma, we screened 66 primary endometrial carcinomas for mutations in the helical and catalytic domains of PIK3CA. We identified a t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

23
322
7
10

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 433 publications
(362 citation statements)
references
References 18 publications
23
322
7
10
Order By: Relevance
“…9 However, recently published studies in endometrial carcinoma demonstrated that coexistent mutations of PIK3CA and PTEN genes are indeed possible. 10 Our case also showed that such combination can also occur in mammary ACC. Furthermore, we showed that reduced expression of PTEN can also occur through increases in promoter methylation.…”
Section: Discussionsupporting
confidence: 66%
“…9 However, recently published studies in endometrial carcinoma demonstrated that coexistent mutations of PIK3CA and PTEN genes are indeed possible. 10 Our case also showed that such combination can also occur in mammary ACC. Furthermore, we showed that reduced expression of PTEN can also occur through increases in promoter methylation.…”
Section: Discussionsupporting
confidence: 66%
“…25,27,28 However, in contrast to other epithelial cancers, such as colorectal 31,36 and breast carcinomas, 37,38 no correlation has been found between the distribution of PIK3CA mutations and grade and stage of disease. Given the recently reported role of PIK3CA mutations in tumor invasion and metastases, 29 we analyzed the PIK3CA status in a large series of endometrial adenocarcinomas and compared the results, between PIK3CA-mutated and PIK3CA-nonmutated groups, with the clinicopathological parameters known to be related to prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 The phosphatidylinositol 3 0 -kinase (PI3K)/AKT signaling pathway is frequently activated in multiple human epithelial cancers, including endometrioid adenocarcinomas. [22][23][24][25] In response to cell-surface receptor signals, PI3K phosphorylates phosphatidylinositol 4,5-biphosphate to generate the second messenger phosphatidylinositol 3,4,5-triphosphate. This, in turn, activates the AKT oncogenic pathway, directly counteracting the actions of the lipid phosphatase PTEN.…”
mentioning
confidence: 99%
See 2 more Smart Citations